x-9=6x+6

Simple and best practice solution for x-9=6x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-9=6x+6 equation:


Simplifying
x + -9 = 6x + 6

Reorder the terms:
-9 + x = 6x + 6

Reorder the terms:
-9 + x = 6 + 6x

Solving
-9 + x = 6 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-9 + x + -6x = 6 + 6x + -6x

Combine like terms: x + -6x = -5x
-9 + -5x = 6 + 6x + -6x

Combine like terms: 6x + -6x = 0
-9 + -5x = 6 + 0
-9 + -5x = 6

Add '9' to each side of the equation.
-9 + 9 + -5x = 6 + 9

Combine like terms: -9 + 9 = 0
0 + -5x = 6 + 9
-5x = 6 + 9

Combine like terms: 6 + 9 = 15
-5x = 15

Divide each side by '-5'.
x = -3

Simplifying
x = -3

See similar equations:

| 0.9+0.3x=2.4 | | 4x+2=142 | | 2x-(3-x)=5+6x | | 2x^2=15-x | | 4x-(x+3)=15 | | 7=(-5-m)+4(6-m) | | -8+(-15)=(-15)+(-8) | | 15x=12(x-3) | | 5x+5+6x=5 | | -3m+4+5m=-6 | | 10x-9=-2x-69 | | 20x^3=50x | | 6(x-9)+x=7(x-9)+9 | | 3x+5=5(x-3) | | (2x+11y)(4x-9y)= | | 0=x^3-19x+18 | | 2x^2+15x=-7 | | 5(c+.80)+6=50 | | 2a+30=4a-4 | | 20+57x-9x^2=0 | | 7(2x-3)=7 | | 2x^2+30x+8=0 | | -4(2x-1)=6(x-2)-2 | | 8(3x+2)-18=-68 | | 7f+5=10(f-7)-3f | | 35-5(2x-3)=20 | | 8x-3x-5+3.2x= | | 5y^2=45 | | 6-3x=2x-24 | | 9y^2-31y-20=0 | | 3a+50=104 | | 10x-3(4+5x)=44 |

Equations solver categories